A 3-D Full-Wave Model to Study the Impact of Soybean Components and Structure on L-Band Backscatter - Kaiser Niknam; Jasmeet Judge; A. Kaleo Roberts; Alejandro Monsivais-Huertero; Robert C. Moore; Kamal Sarabandi; Jiayi Wu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Microwave remote sensing offers a powerful tool for monitoring the growth of short, dense vegetation such as soybeans. As the plants mature, changes in their biomass and 3-D structure impact the electromagnetic (EM) backscatter signal. This backscatter information holds valuable insights into crop health and yield, prompting the need for a comprehensive understanding of how structural and biophysical properties of soybeans as well as soil characteristics contribute to the overall backscatter signature. In this study, a full-wave model is developed for simulating L-band backscatter from soybean fields. Leveraging the ANSYS high-frequency structure simulator (HFSS) framework, the model solves for the scattering of EM waves from realistic 3-D structural models of soybean, explicitly incorporating the interplant scattering effects. The model estimates of backscatter match well with the field observations from the SMAPVEX16-MicroWEX and SMAPVEX12, with average differences of 1–2 dB for co-pol and less than 4 dB for cross-pol. Furthermore, the model effectively replicates the temporal dynamics of crop backscatter throughout the growing season. The HFSS analysis revealed that the stems, pods, and soil are the primary contributors to HH-pol backscatter, while the branches contribute to VV-pol, and leaves impact the cross-pol signatures. In addition, a sensitivity study with a 3-D bare soil surface resulted in an average variation of 8 dB in co- and cross-pol, even when the root-mean-square height and correlation length were held constant. These capabilities underscore the model's potential to provide insights into the underlying dynamics of the backscatter for growing vegetation.